Hilangnya Hak Kepemilikan Atas Tanah yang Terlantar (Analisis Peraturan Pemerintah Nomor 20 Tahun 2021) - Sa’adah, Fatkhiyatus; Adjie, Habib; Saleh, Moh. (UNES Law Review, 2023)
Legal disputes over land rights have become a fundamental and complex problem in the history of the development of agrarian law in force in Indonesia. The inequality that occurs in the pattern of distribution of control, ownership, use and utilization of land, which is also exacerbated by the condition of many land being abandoned by land rights holders, either due to intentional or unintentional factors, has triggered widespread cases of land disputes that have occurred until At the moment. The government itself has attempted to create policies and related regulations, in order to find solutions in resolving cases of ownership disputes over abandoned land. This includes Government Regulation Number 20 of 2021, concerning controlling abandoned areas and land. In this research the author raises two issues, namely, what is the urgency of eliminating ownership rights to abandoned land based on Government Regulation Number 20 of 2021, and what legal remedies can be taken by land rights owners and/third parties who suffer losses due to their abolition rights to abandoned land based on Government Regulation Number 20 of 2021. This research is a form of normative legal analysis (normative legal research), using a statutory approach and a conceptual approach. This research also has important implications in the context of land law, especially in terms of protecting the rights of land owners and encouraging the use of productive land uses. It is hoped that the results will serve as a guide for land ownership rights holders, the government and legal practitioners to better understand the relevant regulations and the impact of loss of ownership rights to land due to abandonment in accordance with the provisions contained in Government Regulation Number 20 of 2021.